Mechanistic insight for improving butenyl-spinosyn production through combined ARTP/UV mutagenesis and ribosome engineering in Saccharopolyspora pogona - Zhao, Xueli; Hussain, Muhammad Hammad; Mohsin, Ali; Liu, Zebo; Xu, Zhixian; Li, Zhanxia; Guo, Weiqun; Guo, Meijin (Frontiers in Bioengineering and Biotechnology, 2024)
Butenyl-spinosyn is a highly effective, wide-spectrum and environmentally-friendly biological insecticide produced by Saccharopolyspora pogona. However, its scale-up is impeded due to its lower titer in wild-type strains. In this work, ARTP/UV mutagenesis and ribosome engineering were employed to enhance the butenyl-spinosyn production, and a stable mutant Saccharopolyspora pogona aG6 with high butenyl-spinosyn yield was successfully obtained. For the first time, the fermentation results in the 5 L bioreactor demonstrated that the butenyl-spinosyn produced by mutant Saccharopolyspora pogona aG6 reached the maximum value of 130 mg/L, almost 4-fold increase over the wild-type strain WT. Furthermore, comparative genomic, transcriptome and target metabolomic analysis revealed that the accumulation of butenyl-spinosyn was promoted by alterations in ribosomal proteins, branched-chain amino acid degradation and oxidative phosphorylation. Conclusively, the proposed model of ribosome engineering combined with ARTP/UV showed the improved biosynthesis regulation of butenyl-spinosyn in S. pogona.